ROMANIAN PARLIAMENTARY ELECTIONS OF 2020. A CASE STUDY OF THE LEGAL FRAMEWORK AND THE CHALLENGES OF THE COVID-19 PANDEMIC - Marius-George COJOCARU (Annals of the "Ovidius" University of Constanţa. Political Science Series)
Romania does not have an electoral code but has a real legislative framework that is the basis for the organization of elections: laws, decisions of the government or of the Permanent Electoral Authority, or decisions of the Central Electoral Bureau. The 2020 parliamentary elections were organized on December 6th, under the special conditions generated by the SARS COV 19 pandemic. It was a complex electoral process involving numerous public institutions and an record number of officials and volunteers. The budgetary effort was approximately 128 million euros. The result: a bicameral legislative body, made up of 330 deputies and 135 senators. The purpose of this paper is to present the way these elections for the constitution of the Legislative Body were organized and conducted, but also to show the need to unify the normative acts that determine the legal framework of the organization of elections. In the first part, I will briefly review the evolution of Romanian parliamentarianism, which begins with the formation of the modern state. The creation of the Romanian democratic state was achieved with considerable difficulty, in a complicated international context, by modernizing the political system, relying on constitutional acts followed by fundamental acts issued under both types of the Romanian political regime (monarchy and republic). In the second part, I will explain the process of organizing the electoral process for the election of members of the Senate and the Chamber of Deputies through the lens of legal provisions, the role of the Permanent Electoral Authority, the Prefect’s institution and the mayors involved in the organization and conduct of elections, but also the activities of electoral experts and of computer operators. We paid special attention to the way elections are organized for the citizens living abroad, both in the polling stations set up with the support of the Ministry of Foreign Affairs, but also to voting by mail.